PERAN KEPEMIMPINAN, IKLIM ORGANISASI DAN PEMBERDAYAAN DALAM MENINGKATKAN KINERJA KOMITE SEKOLAH - E. Kosmajadi (DIALOGIKA, 2019)
The research aims to examine descriptively about leadership, organizational climate, empowerment, and school committee performance and examine verification about the influence of leadership, organizational climate, and empowerment on school committee performance both partially and simultaneously. The method used is descriptive and verification. The population consists of administrators of the State Senior High School Committees in the East Priangan Region with cluster random sampling techniques. Data sources used are primary and secondary data with analysis techniques using path analysis. Descriptive research results prove that leadership, organizational climate, empowerment, and school committee performance are in good condition but there are weaknesses in certain aspects. Verification research results prove that leadership, organizational climate, and empowerment significantly influence the performance of school committees either partially or simultaneously.